PREFERENCE IN SELECTING THE CITY MAYOR ELECTION OF BENGKULU UNDER ETHNIC BACKGROUND - Rahimandani Rahimandani (Universitas Islam Negeri Fatmawati Sukarno, 2018)
This study aims to: first, to find and analyze the correlation and effect of ethnic background of the selecting preferences in the mayor election of Bengkulu City in 2012. Second, to find and analyze whether there was a shift or change in preferences based on ethnic backgrounds in the elections of the Mayor of Bengkulu City between 2007 and2012.This study applied a quantitative approach that classified as causal explanatory descriptive and comparative study. This research is located in the Bengkulu City by taking a sample of 100 respondents by simple random sampling method. To answer the first research objective, statistical analysis is used multinomial logistic regression analysis, whereas to answer the second research purposes used non-parametric statistical analysis of the Mc Nemar test.The results of the data analysis shows there are significance correlation and influence of the ethnic background with preference vote in the election of Mayor and Deputy Mayor of Bengkulu City in 2012. Specifically, ethnic background influence someone to choose candidate for Mayor and Deputy Mayor from ethnic Serawai - Minang, Serawai - Beng- kulu City, and Serawai - Palembang. Then, there was a preference change to choose based on ethnic background in the elections of the city of Bengkulu in 2007 with the election in 2012. Voter preferences based on ethnicity has declined in2012 compared to 2007